Macau higher education expansion in flux: a critical spatial perspective. Issue 6 (2nd November 2017) - Wu, Jinting; Vong, Sou-Kuan
ABSTRACT: In the former Portuguese colony, Macau, higher education is gaining more importance in the post-1999 era in local talent-building and regional integration to safeguard its socioeconomic sustainability. This paper is based on a recent and 'innovative' development in the arena of higher education in the territory, a creation of new space in mainland China for a local public university. By adopting a critical spatial perspective, we examine this idiosyncratic Macau model in three aspects: (1) What kind of power/knowledge production occurs in this new creation of space? (2) How does this new space (re)configure Macau higher education development in both local and global contexts? (3) In what ways does this emergent space re-order the relations between the state, society and school? In employing this spatial stance, we aim to open up understanding of how spatiality affects diverse possibilities in the case of Macau, in global higher education movement more broadly.